EFFICIENT AND SECURE STORAGE OPERATIONS FOR MOBILE CLOUD COMPUTING - Shirinov, Laziz (Science technology&Digital finance, 2023)
This paper presents a holistic security framework for securing data storage in the public cloud, with a focus on lightweight wireless data storage and retrieval devices without exposing the data content to cloud service providers.